2015
DOI: 10.1016/j.topol.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The open-point and bi-point-open topologies on C(X)

Abstract: In the definition of a set-open topology on C(X), the set of all real-valued continuous functions on a Tychonoff space X, we use a certain family of subsets of X and open subsets of R. But instead of using this traditional way to define topologies on C(X), in this paper, we adopt a different approach to define two interesting topologies on C(X). We call them the open-point and the bi-point-open topologies and study the separation and countability properties of these topologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Here U is some given base for X and V is some given countable base for R consisting of bounded open intervals. Now Proposition 2.1 in [6] implies the following proposition.…”
Section: Preliminariesmentioning
confidence: 71%
See 2 more Smart Citations
“…Here U is some given base for X and V is some given countable base for R consisting of bounded open intervals. Now Proposition 2.1 in [6] implies the following proposition.…”
Section: Preliminariesmentioning
confidence: 71%
“…Consider the neighborhood ( Remark 1. In [6], it is shown that the space C ph (X) is completely regular if and only if X 0 is G δ -dense in X if and only if C h (X) is completely regular. Since X 0 ⊆ lc(X), complete regularity of the space C ph (X) implies the complete regularity of the space C kh (X).…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) ⇒ (j). If C h (X) is completely metrizable, then Theorem 3.7 in [9] implies that X 0 is G δ -dense in X. Hence by Theorem 2.3, X is a countable discrete space.…”
Section: Metrizability Of C H (X) and C Ph (X)mentioning
confidence: 94%
“…By Theorems 3.7 and 3.8 in [9], if X 0 is G δ -dense in X, then the spaces C h (X) and C ph (X) are topological groups and hence homogeneous. A space X is called homogeneous if for every pair of points x, y in X, there exists a homeomorphism of X onto X itself which carries x to y.…”
Section: Metrizability Of C H (X) and C Ph (X)mentioning
confidence: 97%